xxx - rosyid, Fathur (Department of Qur'an dan Hadith Faculty of Ushuluddin and Philosophy UIN Sunan Ampel Surabaya, 2012)
Some things that are at issue in this paper is related to the history of the emergence of tafsîr bi al-ra’y, controversy tafsîr bi al-ra’y, and limits the tafsîr bi al-ra’y in the category of al-mahmûd and al-madhmûm. To obtain a valid and accurate data, literature research method used descriptive-analytic approach, in addition to the historical method to get the ideal picture of the history of the emergence of tafsîr bi al-ra’y. The results showed that the tafsîr bi al-ra’y appeared in the range of the fourth century, where social change increasingly prominent and raised several issues that had never happened and questioned at the time of the Prophet Muhammad, sahâbah, and tâbi‘în, until finally sought legitimacy-justification interpretation through the use of reason after not finding answers from history-portfolio earlier. In addition, the rapid advancement of science influenced Islam’s all intertwined with the emergence of diverse disciplines, as well as fanaticism schools due specialties practiced. However, the tafsîr bi al-ra’y accused by the pro-status quo by tafsîr bi al-ma’thûr as misguided interpretation, because the interpreter trying to interpret the word of God without based on science, so this interpretation is prejudice (zann)